Determinan Kemampuan Keuangan Investor Rumah Tangga Di Sumatera Utara - Alistraja Dison Silalahi; Cita Ayni Putri Silalahi; Rukmini; Mohd. Idris Dalimunthe; Yusmalinda; Aria Masdiana Pasaribu (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2024)
This study aims to find and analyze the influence of financial anxiety, financial autonomy, impulsivity, financial attitudes, financial literacy on financial capability, a study of household investor analysis in North Sumatra. This study is a quantitative study, quantitative research is causal. Data analysis techniques use statistical analysis based on partial least square (PLS). The results of the study found that financial anxiety, financial attitudes and digital financial literacy have a positive effect on financial capability, financial autonomy and impulsivity do not affect financial capability